Field-Level Land-Use Adaptation to Local Weather Trends - Ramsey, Steven M.; Bergtold, Jason S.; Heier Stamm, Jessica L. (My University, 2020)
The intersection of agriculture and climate has been well researched for at least the last couple of decades. Largely, the motivation for previous research has been the potential impact on food security for the world's (growing) population. Many studies have predicted unfavorable yield scenarios for some geographic regions. As a result, another common research theme is farmer adaptation to a changing climate. Typically, these studies are concerned with what farmers could or should do to adapt to adverse outcomes. However, research examining whether farmers respond to weather patterns has largely been ignored. Answering this question can help provide more accurate food security analyses: if farmers do respond to changing patterns through cropping decisions, for instance, the global food supply outcome will be different than a world in which they do not respond. This article aims to provide insights into what and how farmers' cropping decisions respond to weather patterns. The study region is a set of eleven Kansas counties. The article provides an important step toward more credible estimates of global food supplies under changing climates and the methods themselves translate to other areas. Results suggest that land-use responses to changing weather patterns will vary across time and space.
Keywords: Adaptation; agriculture; climate change; crop choice; Kansas; Q150